Effects of Commercial Formaldehyde Inclusion and Lysine Level on Pig Performance of 35- to 50-lb Nursery Pigs - R. A. Cochrane; L. G. Sica; J. C. Woodworth; S. S. Dritz; C. R. Stark; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 299 pigs (DNA 400 × 200; initial BW 33.6 lb) were used in a 14-d study to determine the effects of two separate commercial formaldehyde products (Termin-8; Anitox Corp, Lawrenceville, GA and SalCURB; Kemin Industries, Inc., Des Moines, IA) on nursery pig performance. Dietary treatments were arranged in a 3 × 2 factorial design with three formaldehyde inclusions: none vs. 6.5 lb/ton SalCURB vs. 6.0 lb/ton Termin-8 and 2 Lys levels: Standard (1.25% SID Lys) vs. Low (1.10% SID Lys). Formaldehyde treatments were established based on supplier recommendations and diets were treated with supplier-specific equipment. Pens of pigs were balanced by initial BW and randomly allotted to one of six treatments with five pigs per pen and 10 pens per treatment. Overall, there was a tendency (P<0.10) for a formaldehyde source × Lys level interaction to affect ADG and F/G, but not ADFI. Pigs fed diets with standard Lys levels, regardless of formaldehyde source, tended to have similar (P>0.10) ADG to one another, but greater (P<0.10) ADG than pigs fed low Lys levels treated with either formaldehyde source. Furthermore, pigs fed standard Lys levels treated with no formaldehyde or SalCURB tended to have improved (P<0.10) F/G compared to pigs fed standard Lys levels treated with Termin-8 or low Lys levels treated with no formaldehyde or SalCURB. Pigs fed diets with low Lys and treated with Termin-8 tended to have poorer (P<0.10) F/G than all other treatments. Regardless of source or Lys level, the inclusion of formaldehyde in nursery pig diets tended to reduce (P<0.10) ADG and resulted in poorer (P<0.05) F/G. Furthermore, the main effect of formaldehyde source affected (P<0.05) ADG, F/G, and tended to affect (P<0.10) ADFI, with pigs fed Termin-8 performing poorer than those fed SalCURB or no formaldehyde. As expected, Lys level affected (P<0.05) ADG and F/G, but did not alter ADFI (P>0.10). In summary, SalCURB inclusion did not alter nursery pig growth performance compared to the untreated basal diet, regardless of Lys level. However, the inclusion of Termin-8 tended to result in poorer F/G in standard Lys diets and poorer ADG and F/G in low Lys diets compared to an untreated control.
Keywords: formaldehyde; lysine; nursery pigs